Small & Medium Entrepreneurship in European Countries: Main Tendencies of the Development - N. V. Zakharova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article the peculiarities of the small & medium business in European countries are discovered. On the basis of the studying of a great number of scientific works of the Russian & foreign scientists the essential features of this business in Europe are analyzed, also it’s weak & strong pointes comparatively to the big business are highlighted. On the example of France & Switzerland (SWOT-analysis) is proved that each level of regulating of SMB plays a significant role. High importance of the experience of European countries for RF is discovered, also outlined what experience really could be important in the conditions of the Russian Federation.